Study on the Measurement Method of the Crack Local Flexibility of the Beam Structure - Yumin He; Siyu Guo; Xiaolong Zhang (Shock and Vibration)
The crack which appears in the structure can be described by a local flexibility. With the occurrence and propagation of crack, the local flexibility will change. The change can effectively reflect the damage degree of the structure. In this paper, the measurement method of the crack local flexibility of the beam structure is presented. Firstly, a series of sample points are selected at the crack location and the possible value range of the crack local flexibility, and then these sample points are used as input parameters for the dynamic analysis of the beam structure. The vibration equation of beam structure is solved, and the frequency influence surface is drawn. In addition, the vibration signal of the beam is tested, and the first three order natural frequencies can be obtained. Thirdly, these frequencies measured are adopted to cut the natural frequency influence surfaces, and then the first three order natural frequency influence curves are drawn. The intersection points of these frequencies influence curves can indicate the crack local flexibility and the corresponding crack location. This method is suitable for measuring the local flexibility of crack with different shapes and types in the beam structure which have various cross sections.